Determinan work from home dan flexible work arrangements terhadap employee performance PT CTI - Vincentius Kevin Kurniawan (Universitas Tarumanagara, 2023)
The WFH system can be picked up after employees have successfully weathered the pandemic and found increased productivity when most staff are working from home. The purpose of this study is to analyze the phenomenon of declining performance at PT CTI based on financial report data that appears in 2021 by comparing the Work from Home (WFH) and Flexible Work Arrangements (FWA) incentives to Employee Performance (EP). The purpose of this study is to see whether work from home and flexible work arrangements have an influence on employee performance at PT CTI. The research approach used based on the research objectives is explanatory research. The data analysis methodology in this study uses Partial Least Square (PLS). The results obtained that Work from Home has a significant positive effect on Employee Performance. Flexible Working Arrangement has a significant positive effect on Employee Performance. Office-based workers who are still working from home can adapt work as the new normal to return to full-time work on a hybrid basis. Flexible work arrangements can be selected by employees based on different work schedules to meet personal or family needs. This research is important for companies to understand and develop work from home and flexible working arrangements to encourage productive behavior and prevent unproductive behavior from affecting performance. Sistem WFH dapat diambil setelah karyawan berhasil melewati masa pandemi dan menemukan peningkatan produktivitas saat kebanyakan staf bekerja dari rumah. Tujuan penelitian ini untuk menganalisis fenomena penurunan performa pada PT CTI berdasarkan data laporan keuangan yang muncul pada tahun 2021 dengan membandingkan instentif Work from Home (WFH) dan Flexible Work Arrangements (FWA) terhadap Employee Performance (EP). Desain penelitian yang digunakan adalah kuantitatif. Pendekatan penelitian yang digunakan berdasarkan tujuan penelitian adalah penelitian eksplanatori. Metodologi analisis data dalam penelitian ini menggunakan Partial Least Square (PLS). Hasil penelitian diperoleh Work from Home memiliki pengaruh positif signifikan terhadap Employee Performance. Flexible Working Arrangement memiliki pengaruh positif signifikan terhadap Employee Performance. Tenaga kerja berbasis kantor yang masih bekerja di rumah dapat menyesuaikan bekerja sebagai normal baru untuk kembali bekerja penuh waktu secara hybrid. Pengaturan kerja yang fleksibel dapat dipilih oleh karyawan berdasarkan jadwal kerja yang berbeda untuk memenuhi kebutuhan pribadi atau keluarga. Penelitian ini penting bagi perusahaan untuk memahami dan menyusun work from home dan flexible working arrangement untuk mendorong perilaku produktif dan mencegah perilaku yang tidak produktif mengingat peran motivasi kerja dalam memengaruhi kinerja.